2023
DOI: 10.1093/europace/euad096
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of thoracoscopic ablation and radiofrequency catheter ablation for persistent atrial fibrillation as a de novo procedure

Abstract: Aims Limited data are available regarding the efficacy of thoracoscopic ablation as the first procedure for persistent atrial fibrillation (AF). We sought to compare the long-term efficacy of thoracoscopic ablation vs. radiofrequency (RF) catheter ablation as the first procedure for persistent AF. Methods and results Between February 2011 and December 2020, 575 patients who underwent ablation for persistent AF were studied. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…80 Other comparative studies of the propensity score-matched population of thoracoscopic ablation or radiofrequency catheter ablation performed for persistent atrial fibrillation as the first ablative procedure have shown that there is no significant deference in the long-term incidence of tachyarrhythmia recurrence between the two procedures. [85][86][87] Hybrid ablation approach, defined as a bilateral PVI with LAA closure to be performed surgically combined with percutaneous catheter-base endocardial ablation, 3 has been shown to provide better results compared with percutaneous catheter ablation alone in symptomatic AF patients who have failed medical and percutaneous treatment. 88 The procedure may be indicated in a subgroup of symptomatic paroxysmal AF patients with a small LA in whom pharmacological therapy and percutaneous ablation have failed, while the optimal ablation device and approach, the timing of catheter ablation, and other factors are still controversial.…”
Section: Thoracoscopic Af Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…80 Other comparative studies of the propensity score-matched population of thoracoscopic ablation or radiofrequency catheter ablation performed for persistent atrial fibrillation as the first ablative procedure have shown that there is no significant deference in the long-term incidence of tachyarrhythmia recurrence between the two procedures. [85][86][87] Hybrid ablation approach, defined as a bilateral PVI with LAA closure to be performed surgically combined with percutaneous catheter-base endocardial ablation, 3 has been shown to provide better results compared with percutaneous catheter ablation alone in symptomatic AF patients who have failed medical and percutaneous treatment. 88 The procedure may be indicated in a subgroup of symptomatic paroxysmal AF patients with a small LA in whom pharmacological therapy and percutaneous ablation have failed, while the optimal ablation device and approach, the timing of catheter ablation, and other factors are still controversial.…”
Section: Thoracoscopic Af Surgerymentioning
confidence: 99%
“…Patients with a dilated left atrium with or without hypertension were also included in the comparative study; however, no significant efficacy of surgical ablation was demonstrated over catheter ablation 80 . Other comparative studies of the propensity score‐matched population of thoracoscopic ablation or radiofrequency catheter ablation performed for persistent atrial fibrillation as the first ablative procedure have shown that there is no significant deference in the long‐term incidence of tachyarrhythmia recurrence between the two procedures 85–87 …”
Section: Stand‐alone Surgical Af Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, the heightened occurrence of AF has been an important public health challenge. 1 Radiofrequency catheter ablation (RFCA) has become an important treatment for AF, especially in heart failure (HF). 2 As a type of AF, persistent AF (PsAF) was defined as AF lasting more than 7 days.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Europace, Kim et al 7 attempt to address the evidence gap by performing a single-centre retrospective study analysing the incidence of AF recurrence and the composite endpoint of death, stroke, and heart failure hospitalization after performing TA as a stand-alone procedure compared to radiofrequency CA, and hybrid ablation in patients with persistent AF. Among 575 patients included, 281 (49%), 228 (40%), and 66 (11%) underwent TA, CA, and hybrid ablation, respectively.…”
mentioning
confidence: 99%